PERANCANGAN VIDEO DOKUMENTER UBI CILEMBU SEBAGAI MEDIA PROMOSI BUDAYA MASYARAKAT CILEMBU - Khoirul Rizal, Ari Muhamad (Universitas Budi Luhur, 2023)
Cilembu sweet potatoes are already iconic for the people of Cilembu, because most of the land there is yam plantations, and the majority of people work as farmers, but due to the lack of awareness of the urgency of publication, the management of communication media and advertising facilities of the products produced is still not optimal. In fact, if the population is able to manage village resources, especially the uniqueness of the Cilembu sweet potato and is able to introduce it to the wider community, it will certainly be more profitable for the community. This documentary video carries the theme of agribusiness which will present a Cilembu yam farmer with all the information about activities, philosophies and stories about the Cilembu yam itself. All the information contained must be conveyed properly, therefore the documentary video format is an option to package it because it is considered more effective and efficient, besides that the documentary approach makes the author have a wider and more straightforward space to convey ideas and concepts in order to achieve the original purpose of making this video. All aspects of the information conveyed were explored in depth using the method of interviews and observations with Cilembu yam farmers.